2016
DOI: 10.3389/fendo.2016.00163
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Peptidergic Regulation of Stress-Induced REM Sleep Rebound

Abstract: Sleep homeostasis depends on the length and quality (occurrence of stressful events, for instance) of the preceding waking time. Forced wakefulness (sleep deprivation or sleep restriction) is one of the main tools used for the understanding of mechanisms that play a role in homeostatic processes involved in sleep regulation and their interrelations. Interestingly, forced wakefulness for periods longer than 24 h activates stress response systems, whereas stressful events impact on sleep pattern. Hypothalamic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Another important factor inducing late REM sleep surge is stress. Stress induced by restraint, footshock, cold exposure and intermittent hypoxia results in a significant late increase in REM sleep (Horner et al., 1998; Hamrahi et al, 2001; Suchecki, Tiba, & Machado, 2012; Machado & Suchecki, 2016). Volatile anesthetics isoflurane, sevoflurane and halothane may produce delayed REM sleep surge in rat, mouse and human (Knill, Moote, Skinner, & Rose, 1990; Mashour et al., 2010; Pick et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor inducing late REM sleep surge is stress. Stress induced by restraint, footshock, cold exposure and intermittent hypoxia results in a significant late increase in REM sleep (Horner et al., 1998; Hamrahi et al, 2001; Suchecki, Tiba, & Machado, 2012; Machado & Suchecki, 2016). Volatile anesthetics isoflurane, sevoflurane and halothane may produce delayed REM sleep surge in rat, mouse and human (Knill, Moote, Skinner, & Rose, 1990; Mashour et al., 2010; Pick et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In general, short, acute and low‐level stress may increase REM sleep whereas high and extreme stress may have reduced or even less effects on REM sleep (Suchecki et al., 2012). Stress‐induced REM sleep is also gender and aging dependent and may be mediated by pituitary gland hormones such as corticosteroids and prolactin (Bodosi et al., 2000; Descamps & Cespuglio, 2010; Koehl, Battle, & Meerlo, 2006; Machado, Rocha, & Suchecki, 2017; Machado & Suchecki, 2016). Given the complexity of sleep rebound mechanism, genetic background is also likely to be involved (Franken, Chollet, & Tafti, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Their interaction and sequential activation/inhibition contribute to the emergence and regular change of these states. This is provided by the interaction of several systems of neurotransmitters and peptides (Machado and Suchecki, 2016), as certain neurotransmitters contribute to maintaining the state of wakefulness (neurotransmission) of specific neurotransmitters. This helps to maintain the state of wakefulness, and the emergence, deepening and switching of individual phases of sleep (Vassalli and Dijk, 2009;Horner and Beer, 2017).…”
Section: General Concept Of Mammalian Sleep Physiologymentioning
confidence: 99%
“…44,45 Furthermore, isolated loss of REMS is a not common condition in people or animals, although alterations in REMS have been associated with some human health conditions. 39,44 Nonetheless, studies have generally found that REMS deprivation increases nociceptive behavior and impairs the analgesic action of endogenous and exogenous opioids. 34,73,76 Pre-or postsurgery exposure of rats to REMS disruption for 6 h daily on 3 consecutive days did not alter basal responses to mechanical, heat, or cold stimuli but did delay recovery from incision-induced reductions in paw withdrawal threshold to mechanical stimulation.…”
Section: Pain and Sleep: Bidirectional Relationshipsmentioning
confidence: 99%